Pemberdayaan Kelompok Wanita Tani SMART-W2V TUMI : Pengelolaan Limbah Ternak Berbasis Sistem Informasi dan Bisnis Digital - Affriza Brilyan Relo Pambudi Agus Putra; Muhammad Eka Purbaya; Lina Fatimah Lishobrina (Politeknik Piksi Ganesha Indonesia, 2026)
The Women Farmers Group (KWT) of Tumiyang Village holds significant potential in managing rabbit livestock waste, yet faces challenges including limited knowledge, skills, and access to appropriate technology and digital markets. This community service activity aimed to empower KWT economically through the SMART-W2V TUMI Model using two methods: livestock waste technology demonstration and a digital business workshop, involving 41 KWT members. The demonstration covered the production of solid organic fertilizer, liquid organic fertilizer (POC), and biopesticide from rabbit waste. Evaluation results showed significant improvement, with average pre-test scores rising from 70.9% to 81.6% in the post-test, yielding an N-Gain of 0.37 (moderate category). A total of 78.05% of participants achieved the Very Good category. The SMART-W2V TUMI Model proved effective as an integrated approach combining appropriate technology, information systems, and digital business strategies to foster economic empowerment based on local resources in Tumiyang Village.